Bovine infectious abortion: a systematic review and meta-analysis - Hecker, Yanina Paola; González-Ortega, Sara; Cano, Santiago; Ortega-Mora, Luis Miguel; Horcajo, Pilar (Frontiers in Veterinary Science, 2023)
The aim of the present systematic review and meta-analysis was to identify the main infectious agents related to bovine abortion worldwide in the period between 2000 and 2022. First, we investigated the global prevalence of infectious agents related to bovine abortion. For this analysis, only 27 articles detected of a wide panel of agents were included. The random effects model revealed that the estimated prevalence of the abortifacient agents in bovine abortion was 45.7%. The heterogeneity among studies was high, but Egger’s test showed that there was no publication bias, even though the total number of samples analysed in these articles was variable. There was no significant effect of the year of the study publication on the estimated prevalence, although an increasing trend was observed over time, possibly due to the implementation of new diagnostic techniques. Then, we analysed the prevalence of the main transmissible agents in bovine abortion. For this analysis, 76 studies that analysed 19070 cases were included. Some infectious agent was detected in 7319 specimens, and a final diagnosis was reached in 3977 of these, when both the infectious agent and compatible histopathological changes were detected. We found that Neospora caninum was the most detected agent (22.2%), followed by opportunistic bacteria (21.4%), Chlamydiaceae family (10.9%) and Coxiella burnetii (9.5%). Regarding viral agents, bovine herpes virus type 1 and bovine viral diarrhoea displayed similar prevalence rates (approximately 5%). After considering the description of specific histopathological changes, our analyses showed that N. caninum was a confirmed cause of abortion in 16.7% of the analysed cases, followed by opportunistic bacteria (12.6%) and Chlamydia spp. (6.8%); however, C. burnetii was only confirmed as a cause of abortion in 1.1% of the cases. For all agents, the heterogeneity among studies was high, and the subgroup analyses discarded the diagnostic method as the cause of such heterogeneity. This study provides knowledge about the global prevalence of the different infectious agents related to bovine abortion, the most coming of which is N. caninum. In addition, this review reveals the existing deficiencies in the diagnosis of bovine abortion that must be addressed in the future.